Evaluating the Comfort Properties of Single Jersey Knitted Fabrics - Derseh Yilie Limeneh; Addisu Ferede Tesema; Kalavathy Rajan; Noureddine Abidi; Kelem Tiessasie Yilma (Journal of Natural Fibers)
In today’s textile industry, the comfort of a fabric often preponderates its importance in price. The concept of “fabric handle” - the tactile sensation experienced when touching a fabric – plays a crucial role in shaping consumer perceptions and product functionality. This fact greatly influences consumer perceptions of fabric quality during shopping and affects the functionality of textile products in everyday use. This study aimed to explore the comfort properties by using 10 different samples of knitted fabric. Ten single-knit jersey fabrics covering a wider range of commercial uses were used to objectively evaluate the fabric hand properties. The Kawabata evaluation system assessed the mechanical properties, including tensile strength and shearing resistance, bending rigidity, compressional performance, and surface characteristics determining fabric comfort. The material composition has been shown to affect the functional characteristics of fabrics to comply with consumer needs and preferences.